2017
DOI: 10.1007/s00248-017-1066-z
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota of White Shrimp Penaeus vannamei Under Intensive Cultivation Conditions in Ecuador

Abstract: The goal of the study was to characterize the intestinal tract bacterial microbiota composition of Penaeus vannamei in intensive commercial ponds in Ecuador, comparing two shrimp-farming phases: nursery and harvest. Bacterial microbiota was examined by sequencing amplicons V2-V3 of the 16S rRNA using Ion Torrent technology. Archaea sequences were detected in both phases. Sequence analyses revealed quantitative and qualitative differences between the nursery phase and the harvest phase in shrimp intestinal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…We found an enrichment of Caldilinea in all marine shrimps under farm conditions, which is in agreement with the high abundance previously observed of this genus for L. vannamei under intensive cultured conditions ( Gainza et al, 2017 ). The denitrification activity characterizes this bacterium, and interestingly it has been found with high abundance in landfills under chemical-stressed conditions ( Wu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…We found an enrichment of Caldilinea in all marine shrimps under farm conditions, which is in agreement with the high abundance previously observed of this genus for L. vannamei under intensive cultured conditions ( Gainza et al, 2017 ). The denitrification activity characterizes this bacterium, and interestingly it has been found with high abundance in landfills under chemical-stressed conditions ( Wu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…The promotion of changes in the composition of the intestinal microbiota is a key component of the case for using MOS as prebiotics, but this aspect has also been one of the least developed. The composition of the microbiota of shrimp under control conditions is consistent with previous research on this species, agreeing that Proteobacteria is the dominant phylum, with relative abundance levels between 28 and 70% [44][45][46][47][48][53][54][55][56][57] . Other phyla showing high abundance under control conditions were Bacteroidetes (22%) and Actinobacteria (11%), whose values matched those in some of the previous studies; however, overall, those studies showed variable relative abundance levels.…”
Section: Discussionsupporting
confidence: 89%
“…For cultivated crustaceans such as L. vannamei, information on the functionality and structuring of microbiota is very limited. Latterly, advances in NGS have allowed develop research on crustaceans microbiota, as recently addressed in some studies [44][45][46][47][48] . These investigations have been based on modulating the L. vannamei microbiota through nutritional challenges in laboratory conditions.…”
mentioning
confidence: 99%
“…In fish for example, the absence of gastrointestinal microbiota has severe developmental consequences such as late development of epithelial cells, abnormal enterocytes, lower efficiency in the assimilation of proteins and other macromolecules, adverse effect on cholesterol metabolism, depressed immune system, abnormal development of lymphoid tissues associated with the intestine, lower growth and higher mortality (Nayak, ). The understanding of the microbiota of the most important shrimp regarding crustacean aquaculture ( Penaeus vannamei ) remains insufficient compared to vertebrates, including terrestrial livestock and finfish species (Gainza, Ramírez, Ramos, & Romero, ).…”
Section: Introductionmentioning
confidence: 99%